(untitled) (Bangladesh Journal of Medical Science, 2018)
Introduction: Apart from classical functions, vitamin D has autocrine function. Autocrine function of vitamin D has a potential impact on the morbidity and mortality in the Chronic Kidney Disease patients. This study is undertaken to observe probable modality, if present, between post Hemodialysis (HD) decrease in vitamin D levels and clinical deterioration in CKD patients. Method & Material: 63 patients (32 males and 31 females) of Stage – 5 CKD were studied. There vitamin D was estimated before and after HD on first and subsequent maintenance HDs all patients with or without comorbidities. Results: Pre HD total vitamin D levels were ‘deficient’ (58.73%) and ‘sufficient’ in 38.1%, almost equal in patients of both sexes despite intake of supplement containing Calcium and Calcitriol. Post HD vitamin D levels were detected to be markedly low, seems to be ‘washed out’ during HD, in 85.71% of patients (29 males and 27). Vitamin D ‘wash out’ effect was also observed in subsequent maintenance HDs. Females and elderly patients were more prone to vitamin D ‘wash out’. Conventional therapy with vitamin D supplements can replenish but could not prevent its post HD ‘wash out’. Conclusion: It seems, in CKD the deleterious effects of post HD vitamin D deficiency are due to appreciable autocrine dysfunctions resulting in cardio vascular diseases (CVDs) and comorbidities especially diabetes mellitus add to worsening of CVDs, which are the main causes of high morbidity and mortality in these patients. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.652-660